Sit down and drink your beer : regulating Vancouver's beer parlours, 1925-1954 - Campbell, Robert A., 1952- (Studies in gender and history., 2001)
Campbell argues that the regulation of the environment of the classic beer parlour, rather than being an example of social control, is best understood as moral regulation and part of a process of normalization.